Simple determination of human immunodeficiency virus type 1 syncytium-inducing V3 genotype by PCR. - Fouchier, R A (1995)
Human immunodeficiency virus type 1 (HIV-1) phenotype variability plays an important role in the pathogenesis of AIDS. The presence of syncytium-inducing (SI) HIV-1 isolates in infected individuals is associated with a rapid decline of CD4+ T cells, rapid disease progression, and reduced survival time after AIDS diagnosis. The strong association between the SI capacity of HIV-1 and the presence of positively charged amino acid residues at positions 306 and/or 320 in the third variable domain (V3) of gp120 could here be confirmed in 97% of 402 primary HIV-1 isolates, indicating that the V3 genotype may be useful for prediction of the viral phenotype. The V3 DNA sequences revealed a remarkably limited codon usage for the amino acid residues that are responsible for virus phenotype. On the basis of this limited SI-specific DNA sequence variation, four SI-specific oligonucleotides were designed for selective amplification of V3 from SI but not non-SI HIV-1 isolates. This PCR analysis allowed the prediction of the biological phenotype of HIV-1 isolates on the basis of the V3 genotype and may prove to be useful for monitoring SI capacity of HIV-1 isolates in infected individuals.